RECRUITMENT AND RETENTION OF YOUNG LECTURES IN HIGHER EDUCATION INSTITUTIONS OF RUSSIA - Elena A. Berezovskaya; Sergey V. Kryukov (Высшее образование в России)
The article discusses the causes of the unfavorable situation with recruitment and retaining young teachers in the system of higher education of Russia. The universities arenot able or do not consider it necessary to adequately meet the current needs of young teachers, and this leads to «aging» of all the teaching staff of higher school. The authors propose a set of measures on recruitment and retaining of young teachers in university taking into account the structure of their needs.